A PROEMINÊNCIA DAS COOPERATIVAS PARA O AVANÇO DOS OBJETIVOS DE DESENVOLVIMENTO SUSTENTÁVEL (REMUNOM, 2024)
In an urban scenario marked by the vulnerability of many people, resulting from the lack of opportunities, insufficient professional qualifications, and migration from rural to urban areas, cooperatives signal a fundamental role in promoting the SDGs, particularly because their inherent values align with the projections of the SDGs. It appears that cooperatives play a crucial role in promoting the Sustainable Development Goals in vulnerable urban environments, offering opportunities for decent work, economic inclusion, and access to essential services such as education and health. Aligned with the values and goals of the SDGs, they tend to strengthen local economies, reduce inequalities, and improve quality of life. The SDGs are essential for ensuring global sustainable development, which involves protecting the environment, promoting social equality, and ensuring inclusive and sustainable economic growth, especially in the face of challenges of limited resources and increased consumption. In this scenario, this essay elected as its main objective the identification of the influence of cooperatives in achieving the Sustainable Development Goals (SDGs) through bibliographic research and theoretical analysis of scientific articles researched in the Google Scholar database. To this end, the following keywords are used in the search order: "cooperatives," "sustainable development goals," and "sustainability." With the collection and analysis of the data obtained, it was concluded that cooperatives play a significant role in achieving the Sustainable Development Goals in the urban environment, offering solutions to the challenges faced by both the population and the state, thus actively contributing to the construction of a more sustainable and equitable future, highlighting their importance as agents of change in this context.